A Cross-Cultural Study: A Comparison of the Print Advertising in the High-Context and Low-Context Cultures - Zheng, Yi (2018)
This dissertation is a cross-culture empirical study to explore whether the characteristics of Hall’s high-context (HC) and low-context (LC) cultures can be reflected in the print advertising in the automotive industry. Germany is chosen as the representative of LC cultural country. Brazil, South Africa and the United Arab Emirates represent for the HC cultures. The 100 print advertisements from HC culture and LC cultures respectively will be collected and investigated. Meanwhile, the total number of 200 print advertising are all from the same advertising website (Ads of the World) from the recent five years (2013-2018). From applying two theories of the visual complexity and the process of visual appeal on visual analysis and content analysis, there are two primary findings in my study. One is that the print advertising from HC cultures appears greater in visual complexity compared with that of the LC cultures. Another is that, in general, it seems that the print advertising from HC cultures are more likely to have a more indirect process appeal contrasted with that of LC culture. These findings suggest that print advertising in the global market reflect the dominant cultural features in each country which I have investigated.